Acquired Gastric Dieulafoy-Like Lesion due to Aberrant Blood Supply Diverted From the Left Phrenic Artery to an Enlarged Splenule. Issue 4 (14th April 2023) - Lew, Benjamin; Der, Dennis E.; Lim, Brian S.
ABSTRACT: Dieulafoy lesion is an aberrant submucosal vessel that can erode into the overlying tissue leading to hemorrhage. It is a rare but important cause of gastrointestinal bleeding. We present a case of a patient who developed an acquired Dieulafoy lesion 39 years after splenectomy. Abdominal computed tomography showed an aberrant vessel from a branch of the left phrenic artery, coursing through the gastric fundus to supply a splenule. Angiography with embolization of the aberrant vessel resulted in no further bleeding.